2004
DOI: 10.12698/cpre.2004.acrochester
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Study of the Impact of America's Choice on Student Performance in Rochester, New York, 1998-2003

Abstract: Education is a cumulative process. Yet while students' knowledge and skills are built up over time, educational researchers are rarely afforded the opportunity to examine the effects of interventions over multiple years. This study of the America's Choice school reform design is just such an opportunity. Using 11 years of student performance data from Rochester, NY --which includes several years of data before America's Choice began working in the district --we examine the effects of America's Choice on studen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…included only one study of the America's Choice (AC) design, but more recently researchers at the Center for Policy Research in Education at the University of Pennsylvania have carried out several evaluations. A longitudinal matched study in Rochester, NY, found that America's Choice students made greater gains than other students from 1998 to 2003 in reading and math (May, Supovitz, & Perda, 2004). A matched study in Duval Co., Florida (Supovitz, Taylor, & May, 2002) compared America's Choice and other schools on state tests, and results favored the AC schools in writing and, to a small degree, in math (but not reading).…”
Section: America"s Choicementioning
confidence: 99%
“…included only one study of the America's Choice (AC) design, but more recently researchers at the Center for Policy Research in Education at the University of Pennsylvania have carried out several evaluations. A longitudinal matched study in Rochester, NY, found that America's Choice students made greater gains than other students from 1998 to 2003 in reading and math (May, Supovitz, & Perda, 2004). A matched study in Duval Co., Florida (Supovitz, Taylor, & May, 2002) compared America's Choice and other schools on state tests, and results favored the AC schools in writing and, to a small degree, in math (but not reading).…”
Section: America"s Choicementioning
confidence: 99%
“…The changes seemed to contribute to improve students' English language arts (ELA) performance (but not math) when compared with other state-defined low-performing schools. One whole school reform model, America's Choice, commonly in use in New York, shows that the effects of curricular, resource, and organizational changes are promising for student achievement (May, Supovitz, & Perda, 2004). Developed by the National Center for Education and the Economy, this model aims to improve student achievement through rigorous, standardsbased curriculum; safety nets for all students; instructional blocks for literacy, math, and science; a common curriculum core; ongoing student assessments; distributed leadership; and school-embedded teacher professional development.…”
Section: Low-performing Schools Need Extra Resources and Supportmentioning
confidence: 99%